Five little Indians : how they discovered a strange world how they discovered a strange world - La Flescche, Francis (New York : Lancer, 1966)
This edition is for readers for whom English is a second language. It can be anyone whos has learned 2,000 words of english.
Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana